Pterigium berhubungan dengan Sindroma Mata Kering pada Pengemudi Ojek Online - Kartadinata, Erlani; Amalia, Husnun; Adiwardhani, Anggraeni; Witjaksana, Riani; Prasetyaningsih, Noviani; Margo, Eveline; Yohana, Yohana (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Dry eye syndrome (DES) is an eye disease caused by many factors involving the ocular surface, with characteristic damage to tear layer homeostasis accompanied by ocular symptoms due to tear layer instability, hyperosmolarity, damage and inflammation of the ocular surface, and neurosensory abnormalities. Delivery motorbike drivers are often on the streets where the role of environmental factors will be able to pose a risk of experiencing DES. This study aims to assess risk factors associated with the incidence of dry eye syndrome in delivery motorbike drivers. The benefit of this research is to improve public health, especially in preventive behavior against factors associated with dry eye syndrome. Methods This study used observational analytical methods with a cross-sectional research design. The selection of samples by consequential non-random sampling amounted to 124 with the criteria of inclusion of delivery motorbike drivers, exclusion of not using artificial tears eye drops, and not use of contact lenses. Data were collected by filling out a DES risk factor questionnaire and a Tear Break Up Time (TBUT) examination to assess DES. The research data were analyzed using the Chi-Square test. Results This study's results show that subjects with dry eye syndrome are dominated by adults aged 19–44 and male sex. Subjects who experienced DES 76.6%, adult age 78.2%, male 80.6%, no pterygium 66.1%, working period 2-5 years 62.9%, length of work ≥8 hours 94.4%, always using a closed helmet 83.9%, not using protective glasses 39.5%, coffee consumption 71.8%, active smokers 66.1%, using gadgets >6 hours 91.9%. There is no significant relationship between subjects' characteristics and DES (p>0.05). The incidence of DES in pterygium showed significant results (p= 0.001). Conclusions There is a significant relationship between the incidence of pterygium and DES.